دور تغيير نظم وإجراءات العمل في تعزيز الإبداع الإداري دراسة ميدانية بجامعة محمد بوضياف-المسيلة - غزال, فضيل; عسلي, نورالدين (جامعة الوادي - University of Eloued, 2023)
This study aims to know the effect of changing work systems and procedures on administrative creativity, and to clarify the correlation between them. The study included a sample of 140 people from the University of Mohamed Boudiaf-M'sila. The results of the study indicate that the level of changing work systems and procedures is high, and that the level of administrative creativity is also high. It also found that there is a direct correlation R= 0.352 between changing work systems and procedures and administrative creativity
The role of changing work systems and procedures in promoting administrative creativity A field study at Mohamed Boudiaf University - M'sila
مقال
Keywords: تغيير نظم وإجراءات العمل؛ إبداع إداري؛ جامعة المسيلة.; Changing Work Systems and Procedures; Administrative Creativity; University of M'sila